Le bien-être des animaux d'élevage - Mounier, Luc (éditions Quae, 2021)
Animal welfare is one of the major concerns of our society today. Improving the living conditions of farm animals implies changing practices. However, these developments require a harmonization of concepts between the various actors concerned. This booklet synthesizes current scientific knowledge on the sensitivity and consciousness of animals and traces the philosophical and legal history of taking their well-being into account. All this information makes it possible to constitute a common reference for the same basis of understanding of what animal welfare is. This book is aimed not only at students in agricultural or university courses and at livestock professionals, but also at any citizen interested in this issue. It is the first in a series of three booklets devoted to animal welfare. The next two focus on the assessment and improvement of farm animal welfare, respectively.